A REVIEW ON KARAVEERA AND ITS THERAPEUTIC UTILITY - Sudhakar Sruthi; Shenoy Sumanth (International Journal of Applied Ayurved Research, 2020)
Upavisha are the group of drugs which on consumption or administration are relatively less toxic in nature and not as lethal as Mahavisha but produce certain toxic symptoms in the body. Karaveera (Nerium oleander L.) is reported as Upavisha Dravya in classical Ayurvedic pharmacopeias. Four varieties of Karaveera are mentioned according to the text Raja Nighantu but three of them are widely seen all over the world. Though it is a known Cardio-toxic plant (on internal Administration) and all parts of the plant are toxic (particularly seeds and root), it can be used as a therapeutic agent if used after proper Shodhana (purification/processing) both internally and externally. Karaveera being a ‘Upavisha’, has been successfully used in different classical Ayurvedic formulations and indicated in various ailments especially in Skin diseases, Indraluptha (Alopecia areata) etc. In this review an attempt is made to include the overall information about the poisonous plant Karaveera, its Toxicological aspects, Medico-legal aspect and Therapeutic uses.